(untitled) (Revista Ciencia Agraria, 2024)
In the sugar manufacturing process, Pol in cane is a quality parameter. However, there is a problem in its determination, since it is conditioned by the complexity of the calculation, which forced this research to be carried out to provide a feasible, dynamic and economical solution. The objective was to develop a predictive model that allows predicting Pol in cane more quickly and easily from six independent variables: brix in juice, Pol in juice, non-Pol in juice, purity of juice, fiber in cane and cane juice. The research was quantitative with an explanatory and transversal design, where data collected during the 2023-2024 harvest at a sugar mill in the southern region of Guatemala was available. 23,470 records were analyzed for each variable. The results of the multiple linear regression analysis demonstrated that the variables Pol in juice and fiber in cane directly affect the prediction of Pol in cane by evidencing standardized coefficients with statistical significance. A solid mathematical model was generated that attributes high explanatory capacity to the variables Pol in juice and fiber in cane. The formula equation is: Pol in cane = 3.642 + (0.80 x Pol in juice) – (0.242 x fiber in cane). It is concluded that the new proposal for calculating Pol in cane establishes a balance between its simplicity and precision, will facilitate its application and will positively impact decision-making in sugar production.